The Impact of Economic Forces and Social Structures on Environmental Justice in Nigeria - Omoyibo, K. U.; Igbinomwanhia, Osasere Greg (NIU Journal of Humanities; Vol 8 No 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023, 2023)
Environmental justice is a critical and evolving concept that highlights the intersection of environmental issues, social structures, and economic forces. This paper seeks to address the unequal distribution of environmental benefits and burdens among different communities, with a particular focus on marginalised and vulnerable populations. In this paper, we will delve into the profound impact of economic forces and social structures on environmental justice was explored. While undertaking the exploration the multifaceted dynamics that shape our society today was isolated and examined. In the end suggestions and recommendations with the prospect of informing policy and practice was presented. Future investigation akin to the subject matter was also highlighted Keywords: Impact; Economic Forces; Social structures; Environment; Justice; Nigeria